2017
DOI: 10.1007/s00167-017-4579-6
|View full text |Cite
|
Sign up to set email alerts
|

New quantitative radiographic parameters for vertical and horizontal instability in acromioclavicular joint dislocations

Abstract: PurposeThe aim of this study was to identify the most accurate and reliable quantitative radiographic parameters for assessing vertical and horizontal instability in different Rockwood grades of acromioclavicular joint (ACJ) separations. Furthermore, the effect of projectional variation on these parameters was investigated in obtaining lateral Alexander view radiographs.MethodsA Sawbone model of a scapula with clavicle was mounted on a holding device, and acromioclavicular dislocations as per the Rockwood clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 42 publications
1
54
1
4
Order By: Relevance
“…Since clinical data has shown a vast number of persistent horizontal instability following modern arthroscopic AC joint reconstruction techniques [23,24], not only the surgical management but also the clinical assessment have been reconsidered. It has been claimed that parameters assessable on AP and Zanca view do not allow for quantification of horizontal instability, therefore, the use of new radiographic parameters in a single lateral Alexander view has been recently recommended [15,29]. Anyhow, the ESA panel agreed that a true AP view or a bilateral Zanca view without loading the arm are still adequate for a correct diagnosis, with no need of modified Alexander view to seek for horizontal instability.…”
Section: Discussionmentioning
confidence: 99%
“…Since clinical data has shown a vast number of persistent horizontal instability following modern arthroscopic AC joint reconstruction techniques [23,24], not only the surgical management but also the clinical assessment have been reconsidered. It has been claimed that parameters assessable on AP and Zanca view do not allow for quantification of horizontal instability, therefore, the use of new radiographic parameters in a single lateral Alexander view has been recently recommended [15,29]. Anyhow, the ESA panel agreed that a true AP view or a bilateral Zanca view without loading the arm are still adequate for a correct diagnosis, with no need of modified Alexander view to seek for horizontal instability.…”
Section: Discussionmentioning
confidence: 99%
“…15,19 In a previously published in vitro study, we demonstrated that the measured AC-DC distance in lateral Alexander views showed excellent interobserver reliability, as well as higher correlation with CT-measured vertical displacement, when compared with the CC distance. 20 An omission from that study was assessment of the accuracy of AC-DC in measuring the total AC joint displacement, that is, the vector magnitude of combined vertical and horizontal displacement. Although AC-DC showed excellent correlation with CT-measured vertical displacement, while allowing for 20 of variation in projection in 3 dimensions (r ¼ 0.939), further analysis of the data since that publication demonstrated even higher correlation between AC-DC and the total vector of displacement (r ¼ 0.972).…”
Section: Discussionmentioning
confidence: 99%
“…1). 20 The CC distance was measured from the top of the coracoid to the undersurface of the distal clavicle on AP Zanca views, whereas the AC-DC was measured from the middle acromial axis to the dorsal clavicle surface on the lateral Alexander views. All measurements were obtained using picture archiving and communication software (PACS) and presented in millimeters as the difference between the unaffected and injured shoulders.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Einen quantitativen Ansatz der Bestimmung von vertikaler und horizontaler Instabilität an einer isolierten Alexander-Aufnahme haben Zumstein et al [39] vorgestellt. Als völlig neue Messparameter wurden dabei für die vertikale Instabilität die Distanz der "acromion centre line to dorsal clavicle" (AC-DC)…”
Section: Introductionunclassified